2020
DOI: 10.1016/j.jecp.2019.104695
|View full text |Cite
|
Sign up to set email alerts
|

Does group membership affect children’s judgments of social transgressions?

Abstract: Children judge moral transgressions as more serious and more punish-worthy than conventional transgressions (Slomkowski & Killen, 1992; Smetana, 1981). Children also judge the actions of in-group members more favorably than those of out-group members (Aboud, 2003; Zak & Knack, 2001). The current study asked whether children would judge moral and conventional transgressions committed by an in-group member differently when compared to the same acts committed by an out-group member (i.e., act judgments). Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 85 publications
0
4
0
1
Order By: Relevance
“…Yudkin et al (2019) have also found this effect in young children when they are in an authority position to decide on others' transgressions. On the contrary, other studies in adults (Bernhard et al, 2006;Baumgartner et al, 2012;Hewstone et al, 2002;Tajfel & Turner, 1979; and children (Buttelmann & Böhm, 2014;Chapman et al, 2020;Fehr et al, 2008;Gonzalez-Gadea et al, 2020;Jordan et al, 2014) have…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Yudkin et al (2019) have also found this effect in young children when they are in an authority position to decide on others' transgressions. On the contrary, other studies in adults (Bernhard et al, 2006;Baumgartner et al, 2012;Hewstone et al, 2002;Tajfel & Turner, 1979; and children (Buttelmann & Böhm, 2014;Chapman et al, 2020;Fehr et al, 2008;Gonzalez-Gadea et al, 2020;Jordan et al, 2014) have…”
Section: Introductionmentioning
confidence: 87%
“…al., (2019) have also found this effect in young children when they are in an authority position to decide on others' transgressions. On the contrary, other studies in adults (Bernhard, Fehr, & Fischbacher, 2006;Baumgartner, Götte, Gügler, & Fehr, 2012;Hewstone, Rubin, & Willis, 2002;Tajfel & Turner, 1979;Yudkin, Rothmund, Twardawski, Thalla, & Van Bavel, 2016) and children (Buttelmann & Böhm, 2014;Chapman et al, 2020;Fehr et al, 2008;Gonzalez-Gadea et al, 2020;Jordan et al, 2014) have shown that selfish outgroup members are punished more than ingroup selfish members which has been interpreted as a manifestation of ingroup favoritism bias.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similar evidence has been found in the realm of group perception, i.e., affect towards outgroup targets can taint judgements about them (Bodenhausen & Moreno, 2000). For example, transgressions committed by disliked outgroup members tend to be judged more harshly than transgressions by ingroup members (Chapman, May, Scofield, DeCoster, & Bui, 2020). Hence, because affect impacts judgements of and psychological privileged granted to others, one might assume that positive affect towards immigrants is positively associated with their perceived right to be in the UK.…”
Section: Perceived Right To Be Herementioning
confidence: 99%
“…En el ámbito de la percepción grupal se ha obtenido evidencia similar, esto es, el afecto hacia los exogrupos objetivos pueden sesgar los juicios sobre estos (Bodenhausen & Moreno, 2000). Por ejemplo, las transgresiones cometidas por miembros de exogrupos no deseados tienden a ser juzgadas con mayor dureza que las cometidas por miembros del endogrupo (Chapman, May, Scofield, DeCoster, & Bui, 2020). Por tanto, dado que el afecto influye en los juicios y en los privilegios psicológicos que se conceden a los demás, podríamos asumir que el afecto positivo hacia los inmigrantes tiene una relación positiva con el derecho percibido a que permanezcan en el Reino Unido.…”
Section: Derecho Percibido a Permanecer En El Paísunclassified